Features of cerebral circulation in patients with primary open-angle glaucoma with difference type vegetative systeme (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The issue of cerebral circulation of hemisphere is very important in etiology and pathogenesis of primary open-angel glaucoma and for early diagnosis.Purpose. To study the clinical-functional and cerebral circulation of hemisphere criteria for prognosing the development of primary open-angle glaucoma. Materials and methods. Clinical and functional examination was made in 120 patients with primary open-angle glaucoma, the average age 53,6±2,3 years old; 47% male and 52,6 % female, and 60patients of a study group withoutPOAG with disease as follows: vegetative-vascular dystonia, migraine, hypertension, hypotension; mean age 52,4+3,1,48,3 % and 51,7 % males and females respectively. We used neurophysiological methods (the critical flicker fusion frequency CFFFwas studied using the diagnostic module ophthalmic stimulator KNSO2—91 «phosphene», allowing to detect functional changes in the visual analyzer at its different levels) and rheoencephalography according to the standard procedure. Results. We received priority data regarding aspects of cerebral blood filling of hemisphere in patients with primary open-angle glaucoma depending on different types of vegetative system: a statistically significant deviation of blood filling volume of hemisphere in the different stages of glaucoma process more than 20 % that meet the clinical and morphological changes of glaucomatous optic neuropathy at appropriate stages.Conclusions: With the help of mutative analysis it was established clinical criteria of cerebral circulation of hemisphere early diagnosis and prognosis of primary open-angle glaucoma: an increase in the deviation of blood filling volume of hemisphere by 20 % and more; nature of the changes blood filling of hemisphere depends on the type of vegetative system.
Keywords: primary open-angle glaucoma; the deviation of blood filling volume of hemisphere; vegetative system